Day of injury dizziness is related to prolonged recovery following concussion. Issue 11 (25th May 2017) - Luoto, Teemu M; Hänninen, Timo; Parkkari, Jari; Tuominen, Markku; Iverson, Grant L; Vartiainen, Matti; Öhman, Juha
Abstract : Objective: To examine the relation between day of injury concussion symptomology and prolonged recovery. Design: Prospective cohort. Setting: Finnish professional ice hockey league. Participants: SCAT3 baseline and post-injury testing has been mandatory in the Finnish ice hockey league since 2013. Of the reported injuries, between seasons 2013-2016, all cases with a day of injury SCAT3 symptom scale completed were selected. The teams' medical staff confirmed 28 concussions, which were assessed on the day of injury. Outcome measures: The SCAT3 symptom scale was completed on the day of injury. All 22 symptoms were analysed separately. Team medical staff followed up all concussed players and the day of return to play (RTP) was recorder for each athlete. Concussion recovery was considered prolonged if the time of RTP was over 10 days. RTP was analysed as a continuous and a dichotomized variable. Main results: All concussed players (n=28) were Caucasian. The average age was 26.4 years (SD=4.3). The mean Symptom Score was 12.1 (SD=4.3) and the Symptom Severity 26.4 (SD=13.5), respectively. The median time to RTP was 9 days (M=21, SD=47, range=4–248) with 36% of the players being out of play for more than 10 days. There was a significant correlation between Symptom Severity and RTP (p=0.046). Symptom Score was not related to RTP. Dizziness was the only symptom with a consistent statistical relation to longer RTP (Spearman rho=0.4, p=0.029; Mann-Whitney U=4.9, p=0.038; Binary univariate logistic regression: OR=2.6, p=0.04). Conclusions: Acute day of injury dizziness was related to prolonged recovery following concussion. Competing interests: Teemu M. Luoto, Timo Hnninen, Jari Parkkari, Markku Tuominen, Matti Vartiainen, Juha hman: None. Grant L. Iverson has been reimbursed by the government, professional scientific bodies, and commercial organisations for discussing or presenting research relating to mild TBI and sport-related concussion at meetings, scientific conferences, and symposiums. He has a clinical and consulting practice in forensic neuropsychology involving individuals who have sustained mild TBIs (including professional athletes). He has received research funding from several test publishing companies, including ImPACT Applications, Inc., CNS Vital Signs, and Psychological Assessment Resources (PAR, Inc.). He has not received research support from a test publishing company in the past 5 years. None.